Respon Tanaman Daun Tombak (Sagittaria lancifolia) Dalam Cekaman Logam Berat Tembaga (Cu) - Alfin Fatwa Mei Afifudin; Eva Agustina; Nirmala Fitria Firdhausi; Rony Irawanto (Universitas Al Azhar Indonesia, 2022)
One type of heavy metal that pollutes waters is heavy metal copper (Cu). Cu metal is basically an essential metal for living things, but with high levels of Cu metal, it can interfere with the body's metabolic processes. Therefore, there needs to be a solution to overcome Cu metal pollution in the waters. One of them is phytoremediation, or the use of plants to absorb pollutants. Spear leaf plant (Sagittaria lancifolia) is proven to be able to absorb heavy metal copper (Cu). However, the growth response is not yet known in more detail. Therefore, this study aimed to determine the growth response of pike leaf (Sagitaria lancifolia) under stress of heavy metal copper (Cu). This research is an experimental study with a completely randomized design (CRD). The experiment was conducted with 8 treatments (4 treatments with 2 tests) and 3 replications. The 4 treatments were distinguished based on differences in the concentration of Cu metal used, namely 0 mg/L, 1mg/L, 2mg/L, and 3 mg/L. The results showed that exposure to heavy metal copper (Cu) in each concentration variation and detention time variation did not have a significant effect on the growth and morphological conditions of spear leaf (Sagittaria lancifolia) plant, so this plant deserves to be used as an option in recovery efforts of water environment contaminated with heavy metal copper (Cu).Keywords – Response, Lanceleaf arrowhead, Sagittaria lancifolia, Heavy metals, Copper (Cu)